Tindak Pidana Kekerasan Seksual Terhadap Anak Menurut Hukum Hindu - Ida Bagus Subrahmaniam Saitya; I Made Pasek Subawa; I Komang Suastika Arimbawa (Kamaya: Jurnal Ilmu Agama, 2020)
Laws are basically made with the aim of creating security and order in people's lives. Although the law was made to bring order to life, but in reality there are still many people who break them. One of the acts that often happens in society today is the exploitation of children. One of the cases of child exploitation that occurred as a case of child sexual abuse. The contributing factors are internal factors (such as the proximity of the perpetrator to the victim) and external factors (such as being away from the crowd). Because of that, efforts to protect children really need to be done. According to Law Number 23 of 2002, a child is given protection from the womb until he is 18 (eighteen) years old. In this regard, in Hinduism we can also find a legal term known as dharma. Hindu law is divided into two, namely public law (Kantaka Sodhana or Hindu criminal law) and private law (Dharmasthiya or Hindu civil law). The Kantaka Sodhāna can be seen in a subjective sense (ius puniedi) and in an objective sense (ius poenale). Then, regarding the crime of sexual violence against children is not specifically regulated in Hindu law, but the relationship made between men and women who do not have legitimate ties of marriage (marriage), then this act is a crime called Lokika Sanggraha. Therefore, acts of sexual violence against children can be likened to the act of Lokika Sanggraha. In this regard, in Article 171 Ekadaso'dhyayah Mānava Dharmaśāstra, the deed can be blamed and threatened with imprisonment for 12 (twelve) years. The term tapa must be interpreted as imprisonment because in a state a person is imprisoned as suffering as a hermit.